Penerapan Jigsaw untuk Prestasi Belajar SMA Kelas XI pada Fungsi Komposisi dan Fungsi Invers - Hasanah, Nurul (FKIP Universitas Mataram, 2020)
This study aims to improve mathematics learning achievement in the material composition function and inverse function through the application of the jigsaw method to students of class XI IPA SMAN 1 Batulayar. This type of research is a classroom action research model cycle. The focus of research is the application of jigsaw method and learning achievement. The research subjects were 12th grade students of Natural Sciences. Data collection using observations and tests and research data analyzed descriptively. The results of the study are mathematics achievement in the material composition function and inverse function increased through the application of jigsaw method in class XI IPA SMAN 1 Batulayar. The first cycle of the average observation of students activity in the moderately active category (17.67) and observation of the teacher's activity in the active category (18.33) while the mathematics learning achievement in the sufficient category (74.01) but had not yet reached the specified learning completeness category. The second cycle of observation of students activities increased to active categories (22.50) and observations of teacher activities were very active (24.00) while mathematics learning achievements became good categories (81.70). Improving student achievement through the application of jigsaw method is supported by an increase in student learning activities, in form of: active listening to teacher explanations in series, working together in the original group and expert groups, presenting the results of group work, and concluding material about the composition and inverse functions.AbstrakPenelitian ini bertujuan untuk meningkatkan prestasi belajar matematika pada materi fungsi komposisi dan fungsi invers melalui penerapan metode jigsaw pada siswa kelas XI IPA SMAN 1 Batulayar. Jenis penelitian ini adalah penelitian tindakan kelas model siklus. Fokus penelitian adalah penerapan metode jigsaw dan prestasi belajar. Subjek penelitian adalah siswa kelas XI IPA sebanyak 12 orang. Pengumpulan data menggunakan observasi dan tes dan data hasil penelitian dianalisis secara deskriptif. Hasil penelitian adalah prestasi belajar matematika pada materi fungsi komposisi dan fungsi invers meningkat melalui penerapan metode jigsaw di kelas XI IPA SMAN 1 Batulayar. Siklus pertama rata-rata observasi aktifitas siswa pada kategori cukup aktif (17,67) dan observasi aktifitas guru pada kategori aktif (18,33) sedangkan prestasi belajar matematika pada kategori cukup (74,01) tetapi belum mencapai kategori ketuntasan belajar yang ditetapkan.Siklus kedua observasi aktifitas siswa meningkat menjadi kategori aktif (22,50) dan observasi aktifitas guru sangat aktif (24,00) sedangkan prestasi belajar matematika menjadi kategori baik (81,70). Peningkatan prestasi belajar siswa melalui penerapan metode jigsaw di dukung oleh peningkatan aktifitas belajar siswa, berupa : keaktifan menyimak penjelasan guru secara runtun, bekerja sama dalam kelompok asal dan kelompok ahli, mempresentasikan hasil kerja kelompok, dan menyimpulkan materi tentang fungsi komposisi dan fungsi invers.